The Practice of Online Peer Observation in Intermediate Reading Class: A Study at English Language Education of UNP - Dimas Ashariyadi; Senorica Yulia Sari (Journal of English Language Teaching, 2022)
The pandemic of COVID-19 spread around the world forced the educational institution to transform the process of learning from offline learning to online learning. The implementation of online learning becomes a challenge for educational instructors such as teachers and lecturers. Professional development for lecturers is a program done in order to maintain lecturers’ teaching quality and overcome the problems that exist in conducting online learning. The practice of online peer observation aims to support the sharing of practice and builds self-awareness about the impact of one’s teaching practice in order to affect change. The aim of this research is to apply the practice of peer observation in online learning towards the lecturers of intermediate reading class. This research used descriptive study with a qualitative approach. Through purposive sampling, the lecturers who were currently conducting intermediate reading class were selected. Data were collected through 3 stages of teaching observation using observation sheets and interview session. The results showed that the practice of online peer observation could be implemented in a synchronous way through virtual meeting platform. Through teaching observation, the peer was able to observe the lecturer’s teaching process by referring to appropriate aspects of online teaching. Other results are the perceptions of observed lecturers towards the practice of online peer observation in intermediate reading class. The practice of online peer observation was able to be conducted in English Language and Literature Department as a teaching developmental activities. However, there are some aspects of teaching that were missed when conducting peer observation in online, so that there are needed different criteria of observation between the online teaching and the offline one.